Analysis of the Total Value of Productivity Factors in the Manufacturing Industry in East Java - Darmawan, Rizal Rahmat (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
This paper aims to find out total productivity factor (TFP) at east java manufacture by using Stochastic Frontier Analysis. By using industrial survey data at firm level between 2009 and 2010, this paper obtains that east java manufacture has slight negative changes (0,0000006). Furthermore, this paper obtains the result of scale and technological efficiency changes in Cob-Douglas production function for manufacture industry at East Java are 10,13 percent and 3,24 percent, respectively. The average of TFP in east java manufacture industry is 13,4. Textile industry and tobacco industry have lower TFP than other industry, which are 12,8 for each industry. While, metal industry has high TFP than among other industries (15.0). To improve productivity of manufacture industry in East Java, production scale and connectivity between regions need to be lifted up.